Glutamic Acid Decarboxylase Injection Into Lymph Nodes: Beta Cell Function and Immune Responses in Recent Onset Type 1 Diabetes Patients - Casas, Rosaura; Dietrich, Fabrícia; Barcenilla, Hugo; Tavira, Beatriz; Wahlberg, Jeanette; Achenbach, Peter; Ludvigsson, Johnny (Frontiers in Immunology, 2020)
In spite of intensive treatment Type 1 diabetes leads to serious complications. Preservation of residual beta cell function makes the disease milder, facilitates treatment, prevents complications and increase survival. So far immune interventions have had limited effect, and some serious adverse events and risks. In an open pilot trial we aimed to improve efficacy of GAD-alum treatment using lymph-node administration in combination with oral vitamin D. Here we report the clinical effect and focus on biomarkers for response to treatment. Patients (n=12) aged 12-24 years with recent onset of Type 1 diabetes received 4 μg GAD-alum into lymph-node at day 30, 60, and 90, and oral Vitamin D 2000 U/d, day 1-120. Beta cell function was estimated by Mixed Meal Tolerance Tests. GADA, GADA subclasses, GAD65-induced cytokines and proliferation, and T cells markers were analyzed. The treatment was tolerable with no adverse events. Fasting C-peptide and insulin requirement remained stable at 15 months, while HbA1c was lower than baseline. Stimulated C-peptide showed no change at 6 months but declined after 15 months (81% of baseline). Eleven patients remained in partial remission (IDAAC < 9). Patients (n=9) with better clinical outcome had reduced proportion of IgG1 and increased IgG2, IgG3, and IgG4, increased IL-10 secretion, and reduction of proliferation and CD8+ T cells activation. Patients with poorer clinical response had higher baseline levels of GAD65-induced cytokines and T-cell activation, and an increased ratio of effector/central memory T cells. Intra-lymphatic GAD treatment combined with Vitamin D might preserve beta cell function and improve clinical course in T1D. Patients with less benefit have a different quality of immune response both before and after treatment. Trial Registration: NCT02352974, clinicaltrials.gov